Metaplastic Tumour of the Breast: A case presentation - Dewan, Khushboo; Agarwal, Kiran; Pathania, Om Prakash; Sehgal, Shivali (Annals of Pathology and Laboratory Medicine, 2015)
Metaplastic carcinoma (MPC) is a rare breast neoplasm with an incidence of 0-2.5%.Metaplastic spindle cell carcinoma should always be considered in the differential diagnosis of atypical spindle cell proliferations of the breast. We describe the diagnostic challenge posed by a MPC (Spindle cell type) in differentiating it from a Phyllodes tumour (PT) with epithelial hyperplasia on a trucut biopsy. Conventionally, CK and Vimentin co-expression by spindle cells is taken as an evidence for a diagnosis of MPC, but recently, heterogenous CK expression by spindle cells in MPC has been described. Therefore, in such a setting it is not advisable to make a definitive diagnosis of either MPC or PT on a trucut biopsy. However, a few histological and immunohistochemical considerations may help us in deciding the diagnosis. Histologically, blending of squamous cells with spindle cells, presence of extensive lymphocytic infiltrate, keloid-like stromal areas and presence of DCIS, favour the diagnosis of MPC over PT. Absence of CK, EGFR, p63 expression and positive CD34 and bcl-2 expression by spindle stromal cells favours PT over MPC.